2006
DOI: 10.1007/s11095-006-9111-5
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal-Mediated Liposomal Encapsulation of Irinotecan (CPT-11) Stabilizes the Drug in the Therapeutically Active Lactone Conformation

Abstract: Irinotecan is stably entrapped in the active lactone conformation within preformed copper-containing liposomes as a result of metal-drug complexation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 31 publications
(28 reference statements)
0
47
0
Order By: Relevance
“…This strategy incorporates optimization of combination therapies as well as selection of the appropriate patient population to study. Numerous LNP irinotecan formulations are currently under investigation (3)(4)(5)(6)(7)(8)(9)(10), and the success or failure of these formulations will be predicated on a comprehensive understanding of formulation parameters as well as biological activities. Irinophore C™ exhibits substantial therapeutic effects in multiple models of cancer (8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This strategy incorporates optimization of combination therapies as well as selection of the appropriate patient population to study. Numerous LNP irinotecan formulations are currently under investigation (3)(4)(5)(6)(7)(8)(9)(10), and the success or failure of these formulations will be predicated on a comprehensive understanding of formulation parameters as well as biological activities. Irinophore C™ exhibits substantial therapeutic effects in multiple models of cancer (8).…”
Section: Introductionmentioning
confidence: 99%
“…Irinophore C™ exhibits substantial therapeutic effects in multiple models of cancer (8). The mechanisms governing the therapeutic activity of Irinophore C™ involve i) stabilization of irinotecan into its active lactone form (7,11), ii) enhanced irinotecan delivery to sites of tumor growth (8), iii) increased plasma concentration over extended time periods of irinotecan as well as its more active metabolite SN-38 (8,11), and iv) the ability of this LNP irinotecan formulation to promote tumor vasculature normalization (12). A substantial amount of information has been collected to better understand the biological activities of Irinophore C™, and this database continues to expand, as the toxicity of the formulation has recently entered formal evaluation in preclinical safety studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently described a formulation technology that involves the use of entrapped copper ions and a transmembrane pH gradient (acidic inside), which seems to result in significantly improved CPT-11 retention in the liposomes following systemic administration (20). Drugs such as CPT-11 that have protonizable amine groups have been shown to be better retained by liposomes comprising acidic interior buffers (17); further, we have shown that CPT-11 can form a transition metal complex with copper (22). Consequently, following systemic administration, a liposome formulation with a stable internal acidic environment with copper ions mediated substantial improvements in CPT-11 retention, which translated to improved therapeutic activity in a model of colorectal cancer, when compared with carrier systems using pH gradients or copper ion gradients alone.…”
mentioning
confidence: 99%
“…144,191 However, one of the most widely used encapsulation methods employs transmembrane gradients to efficiently load and subsequently stabilize weakly basic amphipathic drugs inside the core of liposomes. These include: (I) simple pH gradients using citric acid solutions, 192,193 (II) ammonium ion gradients employing citrate 194 or sulfate, 195 (III) alkyl, 196 (di-alkyl) or trialkyl ammonium salts, 197 (IV) transition metal concentration gradients (Cu 2+ , Mn 2+ , Zn 2+ and Mg 2+ ) [198][199][200] and (V) transmembrane gradients of drug solubility. 201 The cation entrapped in the liposome interior plays a role either in establishing a pH gradient across the membrane that drives the accumulation of weakly basic drugs into the liposome interior, or directly exchanging with the drug molecule.…”
Section: Active Loading: Gradient Loading Strategiesmentioning
confidence: 99%